Near Me – a location-aware to-do Android application - Garlapati, Deepti Reddy (Kansas State University, 2015)
The growing needs of different products is only being increased from day to day and among these numerous products that each person plan to purchase, it has become a tedious task to keep track of all the products that should be purchased. One such important thing is that, everyone wish to keep track of an item when the location associated with the item is nearby. We have many To-Do applications where we can just note down our day to day needs and things to get. But we might face situations like forgetting to keep track of what we have in our To Do list related to buying an item and when the location associated to the item is nearby, there are high possibilities that we overlook and just forget about purchasing these items. These situations occurred most of the times when I did a small survey among my friends. This difficulty has lead me to rethink and find a solution. The usage of smart phones has become very common these days. Android market which is an open source has helped many people to develop their own applications and these could easily be run on Android smart phones. I thought of developing an android application that helps in tracking not only the To-Do list of the items that a person tracks down to purchase but also stores the location where that item can be purchased. This To-Do app then provide notifications when a person is nearby the location associated with the item. It also triggers an alarm so that the user can easily remember what item he has planned to get in that particular location. The proposed app tries to solve most of the problems by providing an intuitive interface to the user where the user can note down all their planned purchases with location of the products and get reminders about it when passing through that location. The Near Me application is about tracking the items to be purchased or the tasks that are to be done specific to the location. Each to-do item is associated with a date, location and notes. Storing the locations in the application helps the user with timely notifications and alarms according to the location the user is in and the tasks that should be done in that location. Also these To-Do items can also be synced with online storage application like Dropbox.
Keywords: Location Aware To-Do Android application; Computer Science (0984)